COVID-19: The Nursing Administration Response. Issue 4 (October 2020) - Hardt DiCuccio, Margaret; Reynolds, Colleen; Snyder, Amy; Cianci, Nolan
Abstract : The COVID-19 pandemic presented an unprecedented opportunity to test the emergency management plan of one large urban teaching hospital. In this article, a detailed description of the hospital's surge planning process with lessons learned has been provided. Abstract : Supplemental Digital Content is Available in the Text.